2020
DOI: 10.1186/s13068-020-01683-2
|View full text |Cite
|
Sign up to set email alerts
|

Isopod holobionts as promising models for lignocellulose degradation

Abstract: Background Isopods have colonized all environments, partly thanks to their ability to decompose the organic matter. Their enzymatic repertoire, as well as the one of their associated microbiota, has contributed to their colonization success. Together, these holobionts have evolved several interesting life history traits to degrade the plant cell walls, mainly composed of lignocellulose. It has been shown that terrestrial isopods achieve lignocellulose degradation thanks to numerous and diverse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
50
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(57 citation statements)
references
References 73 publications
3
50
0
Order By: Relevance
“…On the other hand, the screening of the bacterial community involved in the breakdown of lignocellulose revealed the presence of four phyla within P. pruinosus, five phyla in A. vulgare, four phyla in Porcellio dilatatus dilatatus and Porcellio dilatatus petiti respectively and three phyla within the freshwater isopod Asellus aquaticus (Bredon et al 2020). The same study showed that Proteobacteria and Bacteroidetes phyla dominate the microbiota of the five studied species especially P. pruinosus where they encode the most part of lignocellulose degrading CAZymes.…”
Section: Discussionmentioning
confidence: 82%
See 4 more Smart Citations
“…On the other hand, the screening of the bacterial community involved in the breakdown of lignocellulose revealed the presence of four phyla within P. pruinosus, five phyla in A. vulgare, four phyla in Porcellio dilatatus dilatatus and Porcellio dilatatus petiti respectively and three phyla within the freshwater isopod Asellus aquaticus (Bredon et al 2020). The same study showed that Proteobacteria and Bacteroidetes phyla dominate the microbiota of the five studied species especially P. pruinosus where they encode the most part of lignocellulose degrading CAZymes.…”
Section: Discussionmentioning
confidence: 82%
“…In accordance, it has been argued that the host origin is the most important factor shaping the microbiota composition in Oniscidea (Dittmer et al 2016;Delhoumi et al 2018). Indeed, the microbiome reacts more rapidly than its host to environmental variability which aids it to evolve and conquer new niches (Bredon et al 2019(Bredon et al , 2020. Moreover, several studies showed that environmental bacteria are involved in Oniscidea performances like reproductive success, growth rate, survival and fertility (Zimmer 2002b;Horváthová et al 2015;Delhoumi et al 2019b) given their high nutritive value (Zimmer & Topp 1998).…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations